A Philosophy of Cover Songs - Magnus, P.D (Open Book Publishers, 2022)
Cover songs are a familiar feature of contemporary popular music. Musicians describe their own performances as covers, and audiences use the category to organize their listening and appreciation. However, until now philosophers have not had much to say about them. In A Philosophy of Cover Songs, P.D. Magnus demonstrates that philosophy provides a valuable toolbox for thinking about covers; in turn, the philosophy of cover songs illustrates some general points about philosophical method. Lucidly written, the book is divided into three parts: how to think about covers, appreciating covers, and the metaphysics of covers and songs. Along the way, it explores a range of issues raised by covers, from the question of what precisely constitutes a cover, to the history and taxonomy of the category, the various relationships that hold between songs, performances, and tracks, and the appreciation and evaluation of covers. This unique and engaging book will be of interest to those working in philosophy of art, philosophy of music, popular music studies, music history, and musicology, as well as to readers with a general interest in popular music, covers, and how we think about them.